Análise morfológica dos folículos primordiais de ovários de ovino criopreservados em EG, DMSO e sua associaçã o - Tsuribe, Patrícia Miyuki; Gobbo, Carlos Alberto Monte [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP] (My University, 2009)
Objective: Compare the cryoprotectants Dimethyl Sulphoxide (DMSO), Ethylene Glycol (EG) and their association for cryopreservation of sheep ovarian cortex. Methodology: Fragments collected from ovaries were divided into 3 parts. 1. One part from sample was destined for analysis of fresh material. 2. The second part was incubated with solution of freezing having 1,5M EG or 1,5M DMSO or 1,5MEG + 1,5M DMSO and washed for dilution of the cryoprotectants. 3. The third part was submitted to cryopreservation using the same cryoprotectans (EG 1,5M; DMSO 1,5M and EG + DMSO 1,5M) and cryopreserved. In all groups, one part of sample was submitted to pre-antral follicles isolation and the remainder was destined to ultra-structural analysis. Results: After isolation of fresh primordial follicles (control), the percentage of viable follicles was 78,9%. The percentage of viable follicles only exposed to cryoprotectants 1,5M EG, 1,5M DMSO and 1,5M EG + 1,5M DMSO was 77,1%, 68,4% and 60,7% respectively. After cryopreservation were 75%, 60% and 55,6% respectively. Ultra-structural analysis of the primordial follicles derived from fresh ovarian fragments or from fragments just exposed to the cryoprotectants showed similar morphology. However, in frozen samples, alterations of mitochondria were observed in all groups. Despite this, the integrity of the remained organelles was preserved in follicles cryopreserved with EG, while that in others groups (DMSO and association) an excess of vacuolizaton in cytoplasm of oocytes and swelling of nuclear membrane was observed indicating degeneration. Conclusion: The Ehilene Glycol seems to be the cryoprotector more adequated for cryopreservation of sheep ovarian tissue.
Morphological analysis of primordial follicles from sheep ovaries cryopreserved in EG, DMSO and their association
Keywords: Cryopreservation; Ovarian follicle; Transmission electron microscopy; dimethyl sulfoxide; ethylene glycol; animal tissue; cell degeneration; cell isolation; cell ultrastructure; cell vacuole; cell viability; comparative study; controlled study; cryopreservation; cytotoxicity; freezing; mitochondrion; nonhuman; ovary follicle; sheep; transmission electron microscopy